SUGGESTOPEDIA METHOD IN THE TEACHING AND LEARNING PROCESS - Bobojonova Zarina Rashidovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
There are four main stages of the activities in suggestopedia method. They are presentation, concert session (active and passive), elaboration, and practice. In the presentation stage, the students are helped to get positive mind that learning is easy and fun. In this stage, the teacher sets the environment of the class as comfortable and cheerful as it could be for the students. In the active concert, the teacher reads a text and is repeated by the students. After that, in the passive concert, the teacher plays some baroque music in the background and she/he reads the text again and the students listen carefully. In the elaboration, the teacher tells the students that they will do something like making film, gaming, etc. after the concert session. In the practice stage, the teacher uses games, puzzles, etc. to review the students View metadata, citation and similar papers at core.ac.uk brought to you by CORE provided by Jurnal Mahasiswa Universitas Negeri Surabaya understanding. This research aims to describe the teacher activities in the presentation stage, concert session, elaboration stage, and in practice stage.